(untitled) (Research, Society and Development, 2022)
In recent years, there has been a growing emphasis on patients and their families’ education on their medical conditions. This has led patients to want more information about their conditions, and in part, health professionals have recognized that a certain self-control of the disease is important for patients. The general objective of this study was to adapt to the Brazilian culture and evaluate the reproducibility of the Bristol COPD Knowledge Questionnaire in patients with chronic obstructive pulmonary disease. The present study dealt with an original questionnaire composed of 65 questions was translated into Portuguese by a professional with mastery in The English language. This first version underwent cultural adaptation. Next, the version adapted to eight patients who answered the questionnaire and evaluated the difficulties with the translated words was evaluated. Next, the version adapted to eight patients who answered the questionnaire and evaluated the difficulties with the translated words was evaluated. This second version in Portuguese culturally adapted underwent a retrograde translation into English by another American translator with mastery in both languages. This English version was compared with the original version by the researchers and then by the author of the original questionnaire. The ICC value of 0.83 was found for the overall evaluation of the two applications of the questionnaire. Evaluated separately, six domains presented the ICC above 0.70, four between 0.60 - 0.69 and three below 0.60. The lowest agreement was observed in the domain regarding etiology and the highest, in oral corticosteroids. We conclude that the Bristol Questionnaire adapted to the Portuguese language of Brazil is easy to understand by patients with COPD and proved to be reproducible.